2014
DOI: 10.3389/fnint.2013.00106
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological blockade of either cannabinoid CB1 or CB2 receptors prevents both cocaine-induced conditioned locomotion and cocaine-induced reduction of cell proliferation in the hippocampus of adult male rat

Abstract: Addiction to major drugs of abuse, such as cocaine, has recently been linked to alterations in adult neurogenesis in the hippocampus. The endogenous cannabinoid system modulates this proliferative response as demonstrated by the finding that pharmacological activation/blockade of cannabinoid CB1 and CB2 receptors not only modulates neurogenesis but also modulates cell death in the brain. In the present study, we evaluated whether the endogenous cannabinoid system affects cocaine-induced alterations in cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 47 publications
(64 reference statements)
3
36
1
Order By: Relevance
“…Additionally, Hu et al (2006) observed that cocaine inhibited proliferation in human fetal neural progenitor cells with simultaneous increase of the cyclin-dependent kinase inhibitor, p21. Moreover, very recently Blanco-Calvo et al (2014) showed that acute administration of cocaine (10 mg/kg) decreases the number of proliferating cells in the subgranular zone, which was prevented by the inhibition of cannabinoid CB1 or CB2 receptors. Cannabinoid receptor blockade was also able to prevent hippocampal-dependent contextual memories induced by cocaine (Blanco-Calvo et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Hu et al (2006) observed that cocaine inhibited proliferation in human fetal neural progenitor cells with simultaneous increase of the cyclin-dependent kinase inhibitor, p21. Moreover, very recently Blanco-Calvo et al (2014) showed that acute administration of cocaine (10 mg/kg) decreases the number of proliferating cells in the subgranular zone, which was prevented by the inhibition of cannabinoid CB1 or CB2 receptors. Cannabinoid receptor blockade was also able to prevent hippocampal-dependent contextual memories induced by cocaine (Blanco-Calvo et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…al. recently reported that pharmacological blockade of CB 1 Rs (by SR144176A) or CB 2 Rs (by AM630) prevents both cocaine-induced conditioned locomotion and cocaine-induced reduction of cell proliferation in the hippocampus of rats (Blanco-Calvo et al, 2014), while Adamczyk et. al. reported that systemic administration of the CB 2 R antagonist SR144528 had no effect on intravenous cocaine self-administration, but attenuated cocaine-induced reinstatement of drug-seeking behavior in rats (Adamczyk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This explains the capacity of addictive drugs such as morphine [3436], heroin [36, 37], methamphetamine [38, 39], cocaine [40, 41], alcohol [42] and cannabinoids [43] to alter hippocampal neurogenic activity. Despite their proven effects on NSPCs, addictive drugs may target different cell types, from quiescent type-1 NSCs to type-3 neuroblasts, by modulating their proliferation, differentiation and survival.…”
Section: Introductionmentioning
confidence: 99%